Most complicated lock pattern-based seismological signal framework for automated earthquake detection - Ozkaya, Suat Gokhan; Baygin, Nursena; Barua, Prabal D.; Singh, Arvind R.; Bajaj, Mohit; Baygin, Mehmet; Acharya, U. Rajendra (Elsevier, 2023)
Background: Seismic signals record earthquakes and also noise from different sources. The influence of noise makes it difficult to interpret seismograph signals correctly. This study aims to develop a computationally lightweight, accurate, and explainable machine learning model for the automated detection of seismogram signals that could serve as an effective warning system for earthquake prediction.Material and method: We developed a handcrafted model for earthquake detection using a balanced dataset of 5001 earthquakes and 5001 non-earthquake signal samples. The model included multilevel feature extraction, selector-based feature selection, classification, and post-processing. Input signals were decomposed using tunable Q wave transform and fed to a statistical and textural feature extractor based on the most complicated lock pattern (MCLP). Four feature selectors were used to choose the most valuable features for the support vector machine classifier. Additionally, voted vectors were generated using iterative hard majority voting. Finally, the best model was chosen using a greedy algorithm.Results: The presented self-organized MCLP-based feature engineering model yielded 96.82% classification ac-curacy with 10-fold cross-validation using the seismic signal dataset.Conclusions: Our model attained high seismological signal detection performance comparable with more computationally expensive deep learning models. Our handcrafted explainable feature engineering model is computationally less expensive and can be easily implemented. Furthermore, we have introduced a competitive feature engineering model to the deep learning models for the seismic signal classification model.
Keywords: MCLP; Earthquake prediction; Explainable feature engineering; Seismological signal processing; XAI